A Case of Castleman's Disease during the Long-Term Course of Membranous Nephropathy. (22nd February 2023) - Nakajima, Shuhei; Nagai, Kei; Sakata, Akiko; Usui, Joichi; Yamagata, Kunihiro; Ueda, Atsushi
Abstract : Concomitant with nephrotic syndrome and multicentric castleman's disease (MCD) has only been described in a limited number of small studies and case reports. Among those, none confirmed the renal pathology prior to the onset of MCD, and none of the cases had a history of nephrotic syndrome. A 76 year-old Japanese man visited a nephrologist because of incident nephrotic syndrome. He had previously experienced three episodes of nephrotic syndrome, the last one 13 years ago, and had been diagnosed with membranous nephropathy by renal biopsy. Apart from these previous episodes, he also suffered from systemic lymphadenopathy, anemia, elevated C-reactive protein, polyclonal hypergammopathy, and elevated interleukin (IL)-6. An inguinal lymph node biopsy revealed CD138-positive plasma cells in the interfollicular region. Based on these findings, MCD was diagnosed. Renal biopsy indicated primary membranous nephropathy with spike lesions and bubbling in the basement membranes and deposition of immunoglobulin (Ig) G, IgA, IgM, and phospholipase A2 receptor along the glomerular basement membrane. Corticosteroid monotherapy successfully reduced the edema, proteinuria, and IL-6, but hypoalbuminemia was not sufficiently improved due to castleman's disease and remission of the nephrotic syndrome was not achieved. Later, tocilizumab was administered for remission induction in another facility. To the best of our knowledge, this represents the first report of Castleman's disease with previously diagnosed membranous nephropathy. This case does not provide a causal mechanism for the pathophysiology, but it may be worth suggesting possible involvement of MCD as a trigger for recurrence of membranous nephropathy.